International Financial Statistics, July 2017. (International Financial Statistics; International Financial Statistics ;, 2017)
This paper discusses about countries where multiple exchange rates are in effect, IMF staff estimates of weighted average exchange rates are used in many cases. A weighted average exchange rate is constructed as an average of the various exchange rates, with the weights reflecting the share of trade transacted at each rate. The notes to the country tables in the monthly issues provide information about exceptions in the choice of the consumer price index and the period average exchange rate index. For a relatively small number of countries, notes in the country tables in the monthly issues indicate where alternative price indices, such as the wholesale/producer price index or a weighted average of several price indices, are used; where data constraints have made it necessary to use weighting schemes based on aggregate bilateral non-oil trade data; and where trade in services (such as tourism) has been taken into account.